Kinetic and equilibrium studies of Pb(II) and Cd(II) adsorption on African wild mango (Irvingia gabonensis) shell - F. A. Adekola; H. I. Adegoke; R. A. Ajikanle (Bulletin of the Chemical Society of Ethiopia, 2016)
The adsorption behavior of NaOH-activated African wild mango (Irvingia gabonensis) shell with respect to Pb2+ and Cd2+ has been studied in order to consider its application to purify metal finishing waste water. The optimum conditions of adsorption were determined by investigating the initial metal ions concentration, contact time, adsorbent dose, pH value of aqueous solution and temperature. The extent of adsorption of metal ions was investigated by batch method using metal concentrations in solution ranging from 5-200 mg/L. The adsorption efficiencies were found to be pH dependent, with maximum metals uptake recorded at pH of 5. The equilibrium adsorption capacity for lead and cadmium ions were obtained from Freundlich, Langmuir, Temkin and DRK isotherms and the experimental data were found to fit best the Langmuir isotherm with values of 21.28 and 40.00 mg/g for Cd(II) and Pb(II) ions, respectively. The Pseudo-second order kinetics model had the best fitting for lead and cadmium adsorption kinetic data. The thermodynamic investigation showed that the adsorption processes of both metals are exothermic. An optimum concentration of 0.05 M HCl was found to be adequate for the regeneration of the spent adsorbent with recovery values of 78% and 71% for Pb2+ and Cd2+ respectively from the spent adsorbent. The results revealed that lead and cadmium are considerably adsorbed on the adsorbent and could be an economic method for the removal of these metals from aqueous solutions.